The articulation of identity in discourses of surveillance in the United Kingdom - Barnard-Wills, David (2009)
This thesis enacts a discursive approach to surveillance in the UK, revealing implications for surveillance theory, governmentality theory, and for political and social identity theories. It demonstrates the importance of a discursive approach to surveillance, as an expansion of assemblage models of surveillance. It finds convergence between government, governance, finance and media discourses, sufficient to conceive of these as forming a shared governmental discourse of surveillance. Governmental, financial and media discourses tend to privilege the assumption that surveillance systems are effective and accurate. This ideological function elides the contingent nature of surveillant practices, presenting them as non-political technological functions. Governmentality accounts of surveillance are supplemented by an expanded understanding of identity as a contested concept, or floating signifier, articulated in particular ways in governmental discourses. The discourse theory informed analysis in this thesis points to a distinct articulation of identity – the governmental surveillant identity – a political attempt to fix the meaning of identity, and construct a surveillance-permeable form that draws upon the privileging of technological truth over human truth. Identity is articulated across many of the five discourses studied as socially vulnerable. The core articulation of the problem of governance is that identity is problematised; unreliable for the proper functioning of governance in society. Because identity is vulnerable and because identity’s ontological nature makes it possible, identity must be checked and secured.